Resistência à tração de retentores intra-radiculares fundidos sumetidos ao acabamento após cimentação com fosfato de zinco - Iglésias, Michele Andréa Lopes (2007)
The refinement of the coronary portion of the intraradicular post cemented constitutes in routine in the clinic. However, the effects of the action of the diamond burn in high rotation on the cement agent are little argued. This study is tested the hypothesis of that the refinement with high rotation an the passed time between the cementation and the accomplishment of the refinement have negative effect in the tensile strength of the intraradicular post cemented in bovine roots. Forty eight bovine roots have been parted with 15mm of length, endodontically treated, confectioned in Cu-Al league, cemented with cement zinc phosphate and divided in 4 experimental groups (n=12). Group A: Without refinement; Group B, C e D submitted the refinement 15, 60 minutes and 24 hours respectively, after the cementation. The assay was carried through in universal machine (EMIC) with speed of 0,5mm/min for all the groups 24 hours after the cementation. The data of tensile strength had been analyzed by the analysis of the variance and test of Bartlet (α=1%). Verified that it did not have significant difference between the groups. Inside of the limitation of this study it can be concluded that the refinement with high rotation and the factor passed time between the cementation and assay did not produce effect of the resistance of the intraradicular posts.